Berbagai Faktor yang Memengaruhi Kejadian Demam Berdarah Dengue di Kota Bandung - Titik Respati; Ardini Raksanegara; Heni Djuhaeni; Asep Sofyan; Dwi Agustian; Lia Faridah; Hadyana Sukandar (ASPIRATOR - Journal of Vector-borne Disease Studies, 2017)
Dengue Haemorrhagic Fever (DHF) reemerged as a significant public health problem, whichreflects the difficulty in sustaining DHF control program. Community-based strategy to control Aedesaegypti breeding sites needs to be understood. The objective of this study is to understand contributedfactors to DHF based on characteristics, the availability of basic sanitation, knowledge, perception, andattitude towards DHF prevention program. A survey conducted to 2035 households in 12 districts and 16villages in Kota Bandung in April to June 2015 using stratified random sampling method. A questionnairewas administered to collect information on variables related to economic status, knowledge on DBD, riskperception and practices associated with Aedes aegypti breeding sites, also basic sanitation facilities. Theanalysis used was correlation and Generalized Estimating Equation (GEE). Results showed that gender, basic sanitation availability, knowledge about dengue in general, knowledge about DHF symptoms, andperception about the disease contribute to dengue cases (p ≤ 0.05). The conclusion of this study is factorscontributed to dengue cases were sex, education, basic sanitation, knowledge about dengue in general,knowledge about DHF symptoms and perception about the disease. Program planning should also include factors and the need for the local community.